2011
DOI: 10.1007/s00401-011-0797-z
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuron disease clinically limited to the lower motor neuron is a diffuse TDP-43 proteinopathy

Abstract: Motor neuron disease (MND) may present as an isolated lower motor neuron (LMN) disorder. Although the significance of pathological 43 kDa transactive responsive sequence DNA binding protein (TDP-43) for amyotrophic lateral sclerosis (ALS) was appreciated only recently, the topographical distribution of TDP-43 pathology in MND clinically isolated to the LMN versus normal controls (COs) is only incompletely described. Therefore, we performed longitudinal clinical evaluation and retrospective chart review of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 36 publications
7
37
0
Order By: Relevance
“…Our pathological results revealed differential UMN involvement between patients with PMA and indicated that PMA and ALS are continuous pathological entities. Regarding immunohistochemical aspects, several studies have revealed that TDP-43 pathology is commonly observed in the cerebral cortices or the subcortical grey matter of patients with PMA 7 8. In our results, TDP-43-positive neuronal or glial inclusions in the motor cortices or hippocampus were common in the clinical ALS and PMA groups and were found even in patients apparently lacking UMN degenerative changes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our pathological results revealed differential UMN involvement between patients with PMA and indicated that PMA and ALS are continuous pathological entities. Regarding immunohistochemical aspects, several studies have revealed that TDP-43 pathology is commonly observed in the cerebral cortices or the subcortical grey matter of patients with PMA 7 8. In our results, TDP-43-positive neuronal or glial inclusions in the motor cortices or hippocampus were common in the clinical ALS and PMA groups and were found even in patients apparently lacking UMN degenerative changes.…”
Section: Discussionsupporting
confidence: 68%
“…Postmortem histopathological studies have revealed corticospinal tract (CST) degeneration in more than half of the patients with MND clinically limited to LMN symptoms/signs 5 6. TDP-43-immunoreactive inclusions have been detected in the LMNs and cortical neurons of patients with PMA 7 8. The disease course of PMA is relentlessly progressive, although somewhat longer than that of ALS 2 4 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Of further relevance, subclinical UMN dysfunction has been reported in progressive muscular atrophy (PMA),101–103 suggesting that PMA may be a phenotype of ALS. While corticomotoneuronal integrity was recently reported to be intact in PMA using a β-band intermuscular coherence technique,104 assessment of cortical function with TMS techniques may be of diagnostic utility, especially in light of presence of subclinical UMN pathology in PMA 102 103…”
Section: Diagnostic Biomarker In Alsmentioning
confidence: 99%
“…The lack of upper motor neuron signs made the diagnosis more difficult. Although a small number of ALS patients are known to exhibit slow disease progression of up to 10 years or more (12)(13)(14) and present with only lower motor neuron signs clinically (14,15), the neuropathy may have partially contributed to the present patient's symptoms, which improved with IVIG therapy. After 45 years of age, when the IVIG therapy no longer achieved any objective improvements, the muscle weakness may have been attributable to ALS, because we did not find any typical CIDP lesions at autopsy, such as onion bulb formation or inflammatory infiltration, although we can not exclude the possibility that such lesions existed in the peripheral nervous system at sites other than those we were able to examine.…”
Section: Discussionmentioning
confidence: 95%